Penegakan Hukum Pelaku Tindak Pidana Narkotika di Lingkungan TNI Berdasarkan UU No. 35 Tahun 2009 Tentang Narkotika Dan UU No. 31 Tahun 1997 Tentang Peradilan Militer - Dian Irawan (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2017)
The danger of narcotics abuse is able to spread to all levels of society, including the Indonesian National Army (TNI). Considering that TNI is a tool of national defense, narcotics crimes committed by members of the TNI will refer to the Criminal Procedure Code and specifically be examined through Military Courts, therefore it is interesting to examine the prosecution of TNI members who commit narcotics crimes under Law Number 35 , 2009 concerning Narcotics Jo. Law No. 31 of 1997 concerning Military Courts and the effectiveness of the application of criminal penalties against law enforcement in the perspective of the objectives of narcotics crime in the TNI. These problems were examined by using research methods through Descriptive Analysis of research specifications and normative juridical approach methods, as well as through qualitative juridical data analysis methods, namely data analysis with concepts or theories without using formulas and numbers. Based on the results of the study, it was found that the process of prosecution of TNI members who committed criminal acts of narcotics was examined by applying Law No. 35 of 2009 concerning Narcotics and the Criminal Procedure Code, while in additional criminal cases the dismissal of military service was based on Article 26 KUHPM. The effectiveness of the application of criminal penalties in the form of dismissals from the military service can provide a deterrent effect in the context of realizing Narcotics-free TNI organizations, the enforcement of discipline and the order of life of TNI soldiers.